A New Method for Assessing Self-Touch Enhancement of the Foot in Stroke Patients with Mobility Problems. (April 2013) - White, Rebekah C; Davies, Anne M Aimola
Patient NG is the first reported case of lower-limb 'self-touch enhancement' following stroke. Mobility problems prevented NG from reaching to touch her foot, thus we used a self-touch rubber-hand paradigm to mimic the conditions of self-administered touch. With vision precluded, NG administered stimulation to a prosthetic limb while the Examiner administered synchronous stimulation to NG's affected left foot. NG detected all stimulation administered with our self-touch paradigm, whereas in the control condition (with NG not involved in administering stimulation), NG had failed to detect one-third of Examiner-administered stimulation. When mobility problems are a barrier to investigating self-touch enhancement, the self-touch paradigm can be used to demonstrate residual tactile sensation following stroke.